The Dialectics of Legal Positivism and the Sociological Jurisprudence School in the Regulation of Human Rights under the 1945 Constitution: A Critical Legal Philosophy Analysis - Putra Alexander Junior; Ali Topan; Isomudin Bandjar; Natsir Asnawi (IHSA Institute, 2026)
The regulation of human rights in the 1945 Constitution of the Republic of Indonesia, particularly Chapter XA, reflects complex dynamics in legal philosophical thought. This study aims to critically analyze the dialectic between legal positivism and sociological jurisprudence in the normative construction of human rights and its implications for constitutional interpretation by the Constitutional Court. The research employs a normative juridical legal method with a critical legal philosophy approach, conducted through a literature review of constitutional norms, relevant statutory regulations, and Constitutional Court decisions related to human rights. The findings indicate that the regulation of human rights in the 1945 Constitution does not represent a single school of legal philosophy, but rather constitutes a paradigmatic synthesis between the normative certainty characteristic of legal positivism and the social responsiveness emphasized by sociological jurisprudence. This philosophical tension is reflected in the variation of interpretive methods adopted by the Constitutional Court, ranging from formalistic to progressive approaches. The study concludes that a constitutional interpretation model based on contextual positivism or responsive formalism is relevant for bridging legal certainty and substantive justice in the protection of human rights in Indonesia